PERANCANGAN IDENTITAS VISUAL DAN KEMASAN UMKM SANDAT BALI DI DESA BATURITI, BALI: Designing Visual Identity and Packaging of UMKM Sandat Bali in Baturiti Village, Bali - Ni Putu Adetya Regina Damayanti, Ni Putu Adetya Regina Damayanti; Ari Rimbawan; Ramanda Dimas Surya Dinata (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
Designing Visual Identity and Packaging of UMKM Sandat Bali in Baturiti Village, Bali. Sandat Bali MSME is a local business specializing in women's sandals that incorporate Balinese art and cultural wisdom. However, it struggles with an inconsistent and less attractive visual identity and packaging, reducing its market competitiveness. This study aims to enhance its brand image through a harmonious design approach by integrating monoline, classic, and Art Nouveau elements that reflect Balinese cultural richness. A bright color palette inspired by sandal flowers and summer, along with elegant serif typography, gives the brand a unique identity. The addition of ornamental borders enhances packaging aesthetics, creating a premium feel. A well-defined visual identity and appealing packaging design can improve market competitiveness, strengthen emotional connections with customers, and enhance brand loyalty. This research highlights how an effective visual identity contributes to successful branding and marketing, emphasizing the importance of aesthetics in boosting consumer engagement with local products.